2012
DOI: 10.1371/journal.pone.0043670
|View full text |Cite
|
Sign up to set email alerts
|

Blunted IL17/IL22 and Pro-Inflammatory Cytokine Responses in the Genital Tract and Blood of HIV-Exposed, Seronegative Female Sex Workers in Kenya

Abstract: BackgroundIdentifying the immune correlates of reduced susceptibility to HIV remains a key goal for the HIV vaccine field, and individuals who are HIV-exposed, seronegative (HESN) may offer important clues. Reduced systemic immune activation has been described in HESN individuals. Conversely, pro-inflammatory T cell subsets, particularly CD4+ T cells producing the cytokine IL17 (Th17 cells), may represent a highly susceptible target for HIV infection after sexual exposure. Therefore, we characterized the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 54 publications
2
50
1
1
Order By: Relevance
“…Women included in the HIV 2 FSW group had been enrolled in the sex worker cohort for at least 3 y, and some of them thus met the criterion of being relatively HIV resistant (24). A low immune activation state can be associated with resistance to heterosexual HIV transmission in the present cohort, as previously identified in blood, cervical mononuclear cells, and cervicovaginal secretions (36)(37)(38). Thus, the relatively low CD4 cell counts and immune activation status that we observed at the genital tissue level for some of the HIV 2 FSW women may reflect and represent this rare phenotype of HIV-resistant individuals.…”
Section: Discussionmentioning
confidence: 55%
“…Women included in the HIV 2 FSW group had been enrolled in the sex worker cohort for at least 3 y, and some of them thus met the criterion of being relatively HIV resistant (24). A low immune activation state can be associated with resistance to heterosexual HIV transmission in the present cohort, as previously identified in blood, cervical mononuclear cells, and cervicovaginal secretions (36)(37)(38). Thus, the relatively low CD4 cell counts and immune activation status that we observed at the genital tissue level for some of the HIV 2 FSW women may reflect and represent this rare phenotype of HIV-resistant individuals.…”
Section: Discussionmentioning
confidence: 55%
“…In a recent study, cervical and peripheral cellular responses to mitogen stimulation were compared between low-risk women and CSWs active in the field for 1 to 38 years. Following mitogen stimulation, PBMC and CMC from CSWs demonstrated a reduced production of Th17/Th22-related cytokines in both compartments, but no difference in the magnitude of the immune response was observed according to duration of sex work [107]. Immunostaining of endocervical biopsies demonstrated that active sex work alters DC phenotypes at the FGT.…”
Section: Impact Of Sexual Activity On the Fgt And Implications For Himentioning
confidence: 88%
“…Decreased levels of T cell activation and host proteins required for HIV-1 replication were observed in HESN sex workers that limit available target cells for viral replication [105]. Factors that affect lymphocytes trafficking to the FGT and that regulate the inflammatory state of the genital mucosa could be key contributors to the induction of immune quiescence and, therefore, protection to HIV [106,107].…”
Section: Hesn and Protection Against Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have examined immune activation in HIV-exposed but uninfected individuals. The majority of these studies support the idea that low levels of immune activation at the time of exposure reduce the risk of HIV-1 infection (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, one recent study indicated that condom use was associated with lower levels of immune activation, potentially confounding some of the prior results (10).…”
mentioning
confidence: 85%